Eksperimental pembakaran droplet pengaruh komposisi asam lemak dan sifat fisika kimia minyak kapas dan jarak pagar terhadap karakteristik nyala api - Dony Perdana (TURBO [Tulisan Riset Berbasis Online], 2023)
Depletion of fossil fuels is required to find alternative fuels that are environmentally friendly and sustainable. This research has been conducted to provide pieces of information on the characteristic of flame on fatty acid content and physicochemical properties of cottonseed oil and jatropha curcas. Droplets combustion of vegetable oil was used in this test, with droplet diameters of 0.3-0.4 mm, which were placed in a K-type thermocouple, then heated with a heating wire. Data collection includes flame evolution, temperature, height and ignition delay time. The results showed that jatropha curcas oil produced a longer flame time of 1206 milliseconds and a temperature of 763Â°C higher than cottonseed oil. The highest flame produced by cottonseed oil was 53.55 mm, while jatropha oil was 50.20 mm. Jatropha curcas oil has a shorter ignition delay than cottonseed oil, 9063 milliseconds and 11375 milliseconds, respectively. Content of various fatty acids and physicochemical properties of vegetable oils fuel affect the characteristics of flames resulting from on combustion process.